2001
DOI: 10.1002/qre.388
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to solving problems of multi‐state system reliability optimization

Abstract: SUMMARYUsually engineers try to achieve the required reliability level with minimal cost. The problem of total investment cost minimization, subject to reliability constraints, is well known as the reliability optimization problem. When applied to multi-state systems (MSS), the system has many performance levels, and reliability is considered as a measure of the ability of the system to meet the demand (required performance). In this case, the outage effect will be essentially different for units with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(82 citation statements)
references
References 54 publications
0
79
0
Order By: Relevance
“…In this paper, an MSS reliability theory will be used, where the binary state system theory is extending to the multi-state case. As is addresses in recent review of the literature for example in (Ushakov, Levitin and Lisnianski, 2002) or (Levitin and Lisnianski, 2001). Generally, the methods of MSS reliability assessment are based on four different approaches:…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…In this paper, an MSS reliability theory will be used, where the binary state system theory is extending to the multi-state case. As is addresses in recent review of the literature for example in (Ushakov, Levitin and Lisnianski, 2002) or (Levitin and Lisnianski, 2001). Generally, the methods of MSS reliability assessment are based on four different approaches:…”
Section: Literature Reviewmentioning
confidence: 89%
“…It was proven to be very effective for high dimension combinatorial problems: see e.g. (Ushakov, 2002), (Levitin, 2001). The universal moment generating function is an extension of the ordinary moment generating function (UGF) (Ross, 1993).…”
Section: Approach and Outlinesmentioning
confidence: 99%
“…Metaheuristics that are used in both the articles compared may find an approximation of the local or global minimum topology, but rarely the exact solution. For information, our UGF model has been tested and compared with ones already conducted [41].…”
Section: Comparative Studymentioning
confidence: 99%
“…What make more complicated to deal with these constraints is the multi-state system (MSS) that represent the wind farm. Even if the MSS reliability measures were intensively studied in [18]- [20], only few articles were found that deal with this reliability optimization including environment effects [21]. Thus, studying the topology optimization of wind farm under constraints of wind, performance and costs turn to be a good research gap.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the problem of availability allocation and optimization can be defined as a multi-objective optimization problem, which aims to maximize system availability and minimize tits cost (Elegbede & Adjallah, 2003). Levitin and Lisnianski (2001) introduced a model in which the cost of designing the system is fixed and its purpose is to optimize system availability. Also, Zio and Bazzo (2011) presented an analysis on level diagrams of Pareto front for the redundancy allocation problem.…”
Section: Introductionmentioning
confidence: 99%